1988
DOI: 10.1016/0266-7681(88)90124-6
|View full text |Cite
|
Sign up to set email alerts
|

Mallet finger: A trial of two splints

Abstract: Over a period of twelve months, 116 cases of mallet finger were allocated randomly to treatment with either a Stack or Abouna splint. The two splints were equally effective, producing a cure or a significant improvement in approximately 50% of cases. However, the Stack splint was much preferred by the patients, who found it more comfortable, more robust and easier to keep clean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 5 publications
3
64
1
1
Order By: Relevance
“…Warren et al compared the Abouna splint with the Stack splint across 116 patients and found no difference in final improvement in extensor lag. 8 Kinninmonth and Holburn compared the Stack splint with a perforated custom-made thermopliable splint across 54 patients. 9 Maitra and Dorani compared the Stack splint with a volar/dorsal malleable aluminum splint.…”
Section: Discussionmentioning
confidence: 99%
“…Warren et al compared the Abouna splint with the Stack splint across 116 patients and found no difference in final improvement in extensor lag. 8 Kinninmonth and Holburn compared the Stack splint with a perforated custom-made thermopliable splint across 54 patients. 9 Maitra and Dorani compared the Stack splint with a volar/dorsal malleable aluminum splint.…”
Section: Discussionmentioning
confidence: 99%
“…2 Multiple studies have shown that conservative treatment provides satisfactory results in those cases in which there is either pure extensor tendon avulsion or fracture-avulsion of less than one third of the base of the distal phalanx. [3][4][5][6][7] Surgery is recommended generally for the unstable lesion that is characterized by an avulsed fragment that involves more than one third of the articular surface or does not reduce with full extension of the distal interphalangeal (DIP) joint. Surgical fixation is also suggested for fragment displacement and/or rotation to prevent joint deformities, posttraumatic arthritis, and stiffness.…”
mentioning
confidence: 99%
“…The duration of treatment is 5 weeks for pediatric patients and 6 weeks for adult patients 2,[17][18] . During this time patients must continuously use the splint and not allow flexion of the DIP joint.…”
Section: Discussionmentioning
confidence: 99%